Philosophy in Colonial India - Deshpande, Sharad.; Deshpande, Sharad. (Sophia Studies in Cross-cultural Philosophy of Traditions and Cultures,, 2015)
This volume focuses on the gradual emergence of modern Indian philosophy through the cross-cultural encounter between indigenous Indian and Western traditions of philosophy, during the colonial period in India, specifically in the 19th and early 20th centuries. This volume acknowledges that what we take ‘Indian philosophy’ or ‘modern Indian philosophy’ to mean today is the sub-text of a much wider, complex and varied Indian reception of the West during the colonial period. Consisting of –twelve chapters and a thematic introduction, the volume addresses the role of academic philosophy in the cultural and social ferment of the colonial period in India and its impact on the development of cross-cultural philosophy, the emergence of a cosmopolitan consciousness in colonial India; as also the philosophical contribution of India to cultural globalization. The issue of colonialism and emergence of new identities in India has engaged the critical attention of scholars from diverse fields of inquiry such as history, sociology, politics, and subaltern studies. However, till today the emergence of modern Indian philosophy remains an unexplored area of inquiry. Much of the academic philosophical work of this period, despite its manifest philosophical originality and depth, stands largely ignored, not only abroad, but even in India. This neglect needs to be overcome by a re-reading of philosophical writings in English produced by scholars located in the universities of colonial India. This edited volume will facilitate further explorations into the presence of colonial tensions as they are visible in the writings of modern Indian academic philosophers like B. N. Seal, Hiralal Haldar, Rasvihary Das,, G. R. Malkani, K. C. Bhattacharyya, . G. N. Mathrani and others.